Key considerations for designing capacity-building interventions to support evidence-based programming in underserved communities: a qualitative exploration. Issue 2 (9th June 2020) - Ramanadhan, Shoba; Galbraith-Gyan, Kayoll; Revette, Anna; Foti, Alisa; Rackard James, Charlotte; Martinez-Dominguez, Vilma; Miller, Elecia; Tappin, Jamiah; Tracy, Natalicia; Bruff, Carmenza; Donaldson, S Tiffany; Minsky, Sara; et al.
Abstract : Program coordinators from community- and faith-based organizations desire trainings on evidence-based programs that include a local expert, account for local resource constraints, and provide ongoing engagement opportunities. Abstract: Increasing the use of evidence-based programs (EBPs) in community settings is critical for improving health and reducing disparities. Community-based organizations (CBOs) and faith-based organizations (FBOs) have tremendous reach and trust within underserved communities, but their impact is constrained by limited staff capacity to use EBPs. This exploratory study sought to identify design and delivery considerations that could increase the impact of capacity-building interventions for CBOs and FBOs working with underserved communities. Data come from a community-based participatory research project addressing cancer disparities in Black, Latino, and Brazilian communities from Greater Boston and Greater Lawrence, Massachusetts. We conducted four focus group discussions with program coordinators in CBOs and FBOs ( n = 27) and key informant interviews with CBO and FBO leaders ( n = 15). Three researchers analyzed the data using a multi-stage coding process that included both prefigured and emergent codes. Key design considerations included embedding customized capacity-building interventions into community networks with local experts, supporting ongoing engagement with the intervention via a range of resources and communication channels, and addressing resource constraints. Regarding the contextual factors that should influence capacity-building intervention content, participants highlighted resource constraints, environments in which EBP use is not the norm, and challenges linking available programs with the multi-level barriers to good health faced by community members. Overall, the study highlights the need for integrated, long-term capacity-building efforts developed in partnership with, and ultimately sustained by, local organizations.